(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Depression is a commonly occurring mental disorder distinguished by sadness, lack of interest, or pleasure in daily activities. Agomelatine is used in the treatment of depression but suffers short half-life and low oral bioavailability. The current research work aims to control the release of drug for longer duration by preparing agomelatine-loaded mesoporous silica nanoparticles incorporated into polymeric microparticles for the treatment of depression. Materials and Methods: Box-Behnken design was used to optimize agomelatine-loaded mesoporous silica nanoparticles prepared by sol-gel method. The drug loading was done by solvent impregnation method. The effect of independent variable such as tetraethyl orthosilicate, CTAB, and NaOH 2 M was analyzed on dependent variable. Double emulsification solvent evaporation was used to incorporate agomelatine-loaded mesoporous silica nanoparticles into ethyl cellulose polymeric microparticles. Results and Discussion: The optimized mesoporous silica nanoparticles showed mean particle size of 166.7 nm, 0.367 PDI, 43.3mV zeta potential, and 78.03% entrapment efficiency. Optimized mesoporous silica nanoparticles were evaluated for FE-SEM, DSC, and XRD. The polymeric microparticles were evaluated for particle size, microscopic evaluation, and in vitro drug release. The polymeric microparticles showed 16% initial burst release followed by a continuous release pattern for 10 h and exhibited Higuchi model with a regression coefficient(R2) of 0.9287. Conclusion: The formulated polymeric microparticles containing agomelatine-loaded mesoporous silica nanoparticles helped to improve the oral bioavailability of the drug and controlled its release rate, which lowers the frequency of dose and is beneficial for the long-term treatment in case of depression.